EMPAGLIFLOZIN MITIGATES CHEMOTHERAPY-INDUCED CARDIOTOXICITY AND ENDOTHELIAL DYSFUNCTION IN BREAST CANCER PATIENTS - Bielinskyi, M.V.; Fedorov, S.V.; Herashchenko, S.B.; Herashchenko, A.S.; Kozlova, I.V.; Havrysh, T.Yu. (World of Medicine and Biology, 2024)
Empagliflozin has recently been suggested as a potential cardioprotective agent for breast cancer patients undergoing chemotherapy, a treatment known for its cardiotoxic effects. This study evaluated the effects of empagliflozin on diastolic function and endothelial health in breast cancer patients without prior cardiovascular disease. Sixty-six female patients were divided into two groups: one receiving empagliflozin during chemotherapy, and a control group. The study found that patients treated with empagliflozin exhibited significantly better preservation of diastolic function, as evidenced by smaller declines in the E/A ratio, E/e’ ratio, and left ventricular ejection fraction. Additionally, endothelial function, measured by flow-mediated dilation, was less impaired in the empagliflozin group. These results suggest that empagliflozin may effectively mitigate the cardiotoxic and endothelial adverse effects of chemotherapy, offering a novel approach to protecting cardiovascular health in breast cancer patients.